Exploring the activities of ruthenium nanomaterials as reactive oxygen species scavengers. (2nd October 2017) - Cao, Gao-Juan; Jiang, Xiumei; Zhang, Hui; Zheng, Jiwen; Croley, Timothy R.; Yin, Jun-Jie
ABSTRACT: Research on noble metal nanoparticles (NPs) able to scavenge reactive oxygen species (ROS) has undergone a tremendous growth recently. However, the interactions between ruthenium nanoparticles (Ru NPs) and ROS have never been systematically explored thus far. This research focused on the decomposition of hydrogen peroxide (H2 O2 ), scavenging of hydroxyl radicals ( OH), superoxide radical (O2 − ), singlet oxygen ( 1 O2 ), 2, 2′-azino-bis(3-ethylbenzenothiazoline- 6-sulfonic acid ion (ABTS + ), and 1, 1-diphenyl-2-picrylhydrazyl radical ( DPPH) in the presence of commercial Ru NPs using the electron spin resonance technique. In vitro cell studies demonstrated that Ru NPs have excellent biocompatibility and exert a cytoprotective effect against oxidative stress. These findings may spark fresh enthusiasm for the applications of Ru NPs under relevant physiologically conditions.